An Assessment of Ovarian Cancer Histotypes Across the African Diaspora - George, Sophia H.; Omotoso, Ayodele; Pinto, Andre; Mustapha, Aisha; Sanchez-Covarrubias, Alex P.; Umar, Usman A.; Umar, Ali B.; Oluwasola, Timothy A.; Okolo, Clement A.; Anthony, Umeh U.; Ukekwe, Francis I.; Bakari, Maisaratu A.; et al. (Frontiers in Oncology, 2021)
Objective: Ovarian cancer in Black women is common in many West African countries but is relatively rare in North America. Black women have worse survival outcomes when compared to White women. Ovarian cancer histotype, diagnosis, and age at presentation are known prognostic factors for outcome. We sought to conduct a preliminary comparative assessment of these factors across the African diaspora. Methods: Patients diagnosed with ovarian cancer (all histologies) between June 2016-December 2019 in Departments of Pathology at 25 participating sites in Nigeria were identified. Comparative population-based data, inclusive of Caribbean-born Blacks (CBB) and US-born Blacks (USB), were additionally captured from the International Agency for Research on Cancer and Florida Cancer Data Systems. Histology, country of birth, and age at diagnosis data were collected and evaluated across the three subgroups: USB, CBB and Nigerians. Statistical analyses were done using chi-square and student's t-test with significance set at p<0.05. Results: Nigerians had the highest proportion of germ cell tumor (GCT, 11.5%) and sex-cord stromal (SCST, 16.2%) ovarian cancers relative to CBB and USB (p=0.001). CBB (79.4%) and USB (77.3%) women were diagnosed with a larger proportion of serous ovarian cancer than Nigerians (60.4%) (p<0.0001). Nigerians were diagnosed with epithelial ovarian cancers at the youngest age (51.7± 12.8 years) relative to USB (58.9±15.0) and CBB (59.0± 13.0,p<0.001). Black women [CBB (25.2 ±15.0), Nigerians (29.5 ±15.1), and USB (33.9 ±17.9)] were diagnosed with GCT younger than White women (35.4 ±20.5, p=0.011). Black women [Nigerians (47.5 ±15.9), USB (50.9 ±18.3) and CBB (50.9 ±18.3)] were also diagnosed with SCST younger than White women (55.6 ±16.5, p<0.01). Conclusion: There is significant variation in age of diagnosis and distribution of ovarian cancer histotype/diagnosis across the African diaspora. The etiology of these findings requires further investigation.